The knowledge of tacit by supervisory technical on the maintenance team - Mohammad Affendy, Omardin; Diyana, Kamarudin; Liu, Yao (Universiti Malaysia Pahang, 2018)
The building maintenance (BM) technical manager's routines aspects of a maintenance are the most challenging aspect of maintenance their facility activities. It requires a focus technical understanding by the building maintenance managers on the factors that contribute to safety performances. This study attempted to develop an explanatory on-site safety performance model for hospital building in Malaysia. The proposed technical BM training was observed through a survey on 14 practitioners. The focus grouped interviewed results supports the conclusion that BM have positive influence on technical routine of the maintenance activities. The findings provide valuable insights for building maintenance industry to develop technical knowledge culture in the future where the knowledge technical could be used as a guideline for training purposes of technical manager's and better maintenance organization and operation of the maintenance activities.